Superior performance of modified pitch-based adsorbents for cyclic methane storage - Mirzaei, S.; Ahmadpour, A.; Shahsavand, A.; Rashidi, H.; Arami-Niya, Arash (2020)
As an alternative approach for natural gas storage at relatively low pressure and ambient temperature, Adsorbed Natural Gas (ANG) has aroused tremendous interest in recent years. However, still, there is a great challenge to find a suitable adsorbent with a high capacity for gas storage. Here in this study, we reported how to prepare an activated carbon with high methane (CH4) uptake using a low cost and abundant precursor such as coal tar pitch (CTP). The effect of two-stage treatment (acidification and carbonization) of CTP on its surface and structural properties, as well as methane adsorption capacity of the final activated carbon products, were explored. Experimental results revealed that the carbon yield of the precursor, porous textural properties, and CH4 adsorption capacity of the adsorbent were efficiently improved via optimization of the pre-treatment conditions. The AC600CTP adsorbent, as an optimum sample, shows the largest capacity of CH4 adsorption on a volumetric basis (184 V(STP)/V) at 25 °C and 40 bar. Based on the authors’ knowledge, the volumetric CH4 capacity of AC600CTP is comparable with the high values reported in the literature among some different classes of the adsorbent. Finally, multiple cyclic operations on AC600CTP at 25 °C and pressure of 40 bar showed the excellent performance of the adsorbent over the dynamic cycle test.